DOCTORAL STUDENTS CREATE AN INTELLECTUAL SYSTEM THAT EVALUATES SCIENTIFIC RESEARCH WORK. - Sulaymanova Shaxzoda (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the creation of an intellectual system designed to evaluate scientific research work, developed by doctoral students. The system leverages advanced algorithms to assess research quality, relevance, and impact, aiming to streamline the evaluation process and ensure objective analysis. The study provides insights into the system’s framework, methodologies, and its potential contributions to academic and industrial settings.